Organizational culture in educational quality in regards of Covid-19 in the Universities of Northern Lima, 2021 - Terán Plasencia Heleny Soley (Revista Iberoamericana de educación, 2021)
Covid-19 has caused great repercussions in education; therefore, the present research aims to demonstrate the impact of organizational culture on educational quality in the context of Covid-19 in the Universities of North Lima, 2021. The study was developed in the quantitative approach of non- experimental, cross-sectional, and causal correlational design. The sample consisted of 127 teachers from the accounting faculty, chosen in a probabilistic and stratified way, and the instruments underwent validity and reliability tests for both variables. The main results obtained were that 57.5% of those surveyed said that the organizational culture is at an optimum level and 61.4% said that the quality of education is efficient. In addition, organizational culture is moderately (Rho=.642) related and has a significant impact (p-value<0.05) on educational quality between 39.7% and 51.6%. The most relevant conclusions were that the statistical analysis corroborated that organizational culture has a significant impact on educational quality, and that organizational culture has a significant impact on the dimensions of the educational quality variable in the universities of North Lima, 2021.